Florida Nursery and Landscape Industry Characteristics Report - Hayk Khachatryan; Melinda Knuth; Alan Hodges; Charlie Hall (EDIS)
This publication summarizes production, marketing, and trade practices for Florida ornamental growers and dealers based on a 2019 national survey by the Green Industry Research Consortium, a multi-state research project under the USDA-National Institute for Food and Agriculture. The most recent survey collected information on business practices for the fiscal year 2018-2019 in all 50 states.